1985
DOI: 10.1111/j.1813-6982.1985.tb01015.x
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Measures of Exchange Rates and Exchange Rate Policy in South Africa

Abstract: (1) OVER THE PAST SEVERAL YEARS the flexibility of exchange rate policy in South Africa has been increasing. Officials have frequently indicated that a 'market based' exchange rate policy is being followed which the De Kock Commission (1985) has described as a managed float. Certainly fluctuations in the rand exchange rate against all major currencies have increased in the recent past. With this greater variability, however, it has become increasingly difficult to determine exactly what has been happening to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
1991
1991

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…It is interesting that Brazil actually depreciated its currency in real terms over this period. South Africa *(9) -6,5 Holden and Holden (1985) calculated the real effective exchange rate for South Africa for the period January 1973 to August 1985, using nominal effective exchange rates and consumer price indices. When these monthly data were averaged for each year, it was found that the devaluation of the rand in September 1975 effected a 6 per cent real depreciation of the currency, while the rise in the price of gold from 1976-80 contributed to appreciating the currency in real terms by 12 per cent.…”
Section: Exchange Rate Policiesmentioning
confidence: 99%
“…It is interesting that Brazil actually depreciated its currency in real terms over this period. South Africa *(9) -6,5 Holden and Holden (1985) calculated the real effective exchange rate for South Africa for the period January 1973 to August 1985, using nominal effective exchange rates and consumer price indices. When these monthly data were averaged for each year, it was found that the devaluation of the rand in September 1975 effected a 6 per cent real depreciation of the currency, while the rise in the price of gold from 1976-80 contributed to appreciating the currency in real terms by 12 per cent.…”
Section: Exchange Rate Policiesmentioning
confidence: 99%
“…The pressures are likely to be reflected by unstable international capital flows which could upset foreign exchange markets. In these circumstances a small open economy such as that of South Africa, without a well structured, diversified export sector (Holden and Holden, 1985), is probably better off with a dual exchange 1987 SAJE v55(3) p208…”
Section: Exportsmentioning
confidence: 99%